Business law : the ethical, global and e-commerce environment - Mallor, Jane P. (McGraw-Hill/Irwin, 2010)
Suitable for the two-term business law course, this book reveals cases that are excerpted and edited by the authors. It retains the language of the courts. It includes a mix of actual and hypothetical cases